The Negro and Methodist Union - Carter, Paul Allen (Church history, 1952)
The schism in the Methodist Episcopal Church in 1844, and her reunion in 1939, fall into a pattern remarkably similar to that of the great schism and reunion of the United States. The antislavery movement possessed religious overtones of the same evangelical temper characteristic of Methodism; and the centralized—constitutional, if you will— structure of Methodism exposed it to federal-versus-regional stresses similar to those that divided the nation. There is the significant difference that the Northern and Southern Methodists parted amicably, and did not become involved in partisan bitterness until after the adjournment of their last General Conference together, but otherwise the parallel is complete: general acceptance of the principle of emancipation by the founders both of church and nation; with the renascence of slavery, the recession of this view, marked by a series of compromises in General Conference as in the Congress; the rise, and unpopularity, of militant abolitionism; a dramatic revival of partisan concern, marked by an acute constitutional debate growing sectional irreconcilability: schism; conflict—and an eventual resolution of the breach in terms of the tacit recognition by the North of the principle of segregation.